The co-evolution of safety cultures and crisis management capacities in maritime trading systems - Barnes, P.; Oloruntoba, Richard (2013)
This chapter investigates an alignment of issues in security, risk and vulnerability analysis to present a comprehensive framework for designing an integrated safety-crisis culture across maritime supply chains and associated workplaces. The framework examines systems and processes for training, including needs analyses, covering crisis management capacities that enhance vulnerability analysis in maritime trading systems and the security assurances of supply chains. A combination of primary and secondary data sources from maritime and related industries in Europe and the Asia-Pacific region will be applied in a comparative analysis of practices and theoretical approaches to safety and crisis response. The scope of the chapter is limited to the requirements for designing, developing and implementing safety and crisis management cultures in organizations across maritime supply chains. The study reinforces the unique security challenges in the maritime operating environments and in regional port settings. It also details a selection of innovative strategies for mitigating these issues and challenges and in generating a capacity to anticipate some types of crisis. In summary, the authors find the need for development of flexible—yet specific practices—that must be embedded in the operational and managerial repertoire of commercial participants of maritime supply chains internationally. These practices (via the organizational culture) must be adaptive to emergent conditions yet grounded in professional knowledge.